Educational evaluation: Forms for use in pedagogical practice - Freitas, Sirley Leite; Da Costa, Michele Gomes Noé; De Miranda, Flavine Assis [UNESP] (My University, 2014)
In this article we discuss some evaluation approaches. It presents concepts related to diagnostic, formative and summative evaluation according to several authors. It reviews the traditional approach in which evaluation is used with punitive and social control purposes. It also presents the mediating view of learning in a continuous process of action-reflection-action in relation to the pedagogical practice. Finally, it proposes to overcome the classificatory and punitive view of evaluation as a measure for classification of knowledge and social exclusion.
Avaliac¸ão educacional: Formas de uso na prática pedagógica
Keywords: Evaluation approaches; Pedagogical practice; Social exclusion